Abadeha the Philippine Cinderella - De La Paz, Myrna J. (Los Angeles, California Pazific Queen Communications, 1991)
In this version of Cinderella, set in the Philippines, Abadeha endures abuse by her stepmother before being helped by the Spirit of the Forest and becoming the bride of the island chieftan's son.
Fi-11697g donated by Prof. Mamoru Tsuda.
Keywords: Folklore -- Philippines; Fairy tales